Infants’ Hemodynamic Modulation in the Temporal Region - Tsuji, Yuki; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Human Neuroscience, 2022)
This study examined whether 8-month-old infants' hemodynamic responses in the temporal region were modulated by repeated presentation of “Peekaboo” by using functional near-infrared spectroscopy (fNIRS). Previous studies have shown that infants’ temporal region responds to faces (e.g., Otsuka et al., 2007). A recent electroencephalography study showed that the neural activity of infants was modulated by repeated presentation of “Peekaboo.” Some fNIRS studies also revealed that the movie of “Peekaboo” activated the hemodynamic response of the temporal region in infancy. However, no studies have shown the hemodynamic modulation of the temporal region according to the repeated presentation of “Peekaboo” in infants. In order to examine whether the hemodynamic responses of the temporal region were modulated by repeated presentation of “Peekaboo,” we compared the activity of the temporal region between the early and late trials. We set long and short delays before face-presentation. The results showed that the concentration of oxy-hemoglobin in the right occipitotemporal region (Ch 21) in both conditions increased after the presentation of “Peekaboo” relative to the baseline. Moreover, in the long delay condition, the hemodynamic modulation of the right occipitotemporal region was induced according to the repeated presentation of “Peekaboo” in infants.